Content Analysis in “Podcast” Rintik Sedu to Captivating Listeners - Diniar, Syafiya Puspa; Febriana, Poppy (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2023)
Rintik Sedu is a popular podcaster on Spotify whose channel consistently ranks first with the most listeners. Starting in May 2019, the channel has gained a high rating of 4.9/5 and topped the charts in October and subsequent months. This article aims to discuss the development of podcasts in Indonesia. We studying the content and communication methods of the Rintik Sedu podcast to attract millions of listeners on Spotify, and the opportunities for Indonesian podcasters and listeners in utilizing digital podcast media, including providing information, offering personal experiences, alternative media creation, monetization possibilities, complementing traditional radio and video platforms, and providing safe and comfortable long-term access. research methodology employed, which is content analysis using a descriptive approach to study the Rintik Sedu podcast's content in the Spotify streaming application. The researcher method follows the steps outlined by Philip Mayring for analyzing the podcast's content, categorizing the audio content based on episode titles, examining the aspects of the communicator, and interpreting the meaning of the categories. The analysis revealed three main themes: lonely love, love that is too late, and past love, indicating that listeners preferred content focused on romance, particularly stories about unrequited love, missed opportunities, and past relationships. The researcher suggests that these categories can be further explored and tested in future studies related to content analysis in specific topics.